A Case Study on the Supreme Hotel Sdn.Bhd. Strategic Management for Organizational Competitiveness - Woo, Pak Yuan (1997)
The objective of this case study are divided into two parts. In Part A of the case study, the introduction to the company background and the functions of each department will be discuss. The probable causes to the problem will be fwther discuss in this part by retenng to the appendix. In Part B of the case study, the discussion will be ba.."iC on methodology used, problem solving and to identify the strengths , weaknessess , opportunities and threats bcing by the company . The clements that need to be evaluate are the company financial , op{''fation , sales and marketing and lastly the human resources and training. It is very important for these elements to be analyze so that it can help to determine the level of competitivt.'11CSS and limitation the company have. After analyzing each of the element , a suggestive recommendations will be given on how the company can expand , safeguard its market share , improving employer -employee relationships and the training and development programmes for its staffs . The ll"iage of weightage methodology to analyze the internal factors (Finance , Managem(''1ltlHuman Resources , Operation and Marketing) and external strategic factors (political, Economy, Socio-CulturaJ, Technology, Competitor,Consumer, Substitute,New Entrance, Government). 1he SWOT analysis i., use to guide the company on how to maximize its strengths and opportunities to overcome itr;; weaknessess and threat". The SWOT matrix is use to guide the company to rank its five most important SWOT so that a clearer direction of the company can be narrow down further. Finally , the usage of Strategic Positioning and Action EvallU1tion model (SPACE) to detennine the direction the company should go for.